Time and information overload as variables in organisational communication - Arnold de Beer; Anske Basson (Communicare)
In the field of organisational communication much emphasis is placed on the verbal aspects of human communication. A consideration of the literature shows scant attention is being paid to non-verbal aspects. Time as a single non-verbal variable, however, is given even less attention. This is remarkable when developments in the field of information processing through computerized technology is considered. In this paper the importance of time considered against the backdrop of ever increasing technological change and information overload, is discussed. It will be argued that much more research should be done to place the time variable in true perspective within the field or organisational communication.